2021
DOI: 10.1021/jacs.1c02029
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Kinetics: Bimolecular Reactions of Carbonyl Oxide by a Triple-Level Strategy

Abstract: Criegee intermediates in the atmosphere serve as oxidizing agents to initiate aerosol formation, which are particularly important for atmospheric modeling, and understanding their kinetics is one of the current outstanding challenges in climate change modeling. Because experimental kinetics are still limited, we must rely on theory for the complete picture, but obtaining absolute rates from theory is a formidable task. Here, we report the bimolecular reaction kinetics of carbonyl oxide with ammonia, hydrogen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 111 publications
3
69
1
Order By: Relevance
“…To choose the lower level, we tested the MN15-L, 72 M11-L, 73 M06-2X, 74 and M06CR 61 density functionals with the MG3S 75 basis set. We choose M11-L from among these trial functionals because it showed best agreement with the higher-level calculations.…”
Section: Theoretical Methods and Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…To choose the lower level, we tested the MN15-L, 72 M11-L, 73 M06-2X, 74 and M06CR 61 density functionals with the MG3S 75 basis set. We choose M11-L from among these trial functionals because it showed best agreement with the higher-level calculations.…”
Section: Theoretical Methods and Strategiesmentioning
confidence: 99%
“…Furthermore, previous investigations have shown that higher excitation levels than CCSD(T) (we call them beyond-CCSD(T) calculations) are necessary for reliable results due to the strong multireference characters of Criegee intermediates. [59][60][61][62][63][64][65] In this article, we use our recently developed dual-level rateconstant strategy 60,[66][67][68] and system-specific quantum Rice-Ramsperger-Kassel theory (SS-QRRK) to obtain rate constants for the CH 2 OO + CH 3 C(O)CH 3 reaction under atmospheric temperature and pressure conditions. We use the W3X-L composite method that goes beyond CCSD(T) as the higher level in the dual-level calculations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To select a method for direct dynamics calculations, we used the benchmark to test three exchange-correlation functionals: MN15-L, M06-2X, and M06CR–in all three cases with the MG3S basis set. As a result of these tests, we selected MN15-L/MG3S for the cyclization reaction and M06-2X/MG3S for the stereoisomerization reaction.…”
Section: Methodsmentioning
confidence: 99%